Lower levels of high-density lipoprotein cholesterol are associated with increased cardiovascular events in patients with acute coronary syndrome receiving contemporary lipid-lowering therapy. (25th November 2020) - Nakazawa, M; Arashi, H; Inagaki, Y; Otsuki, H; Yamaguchi, J; Ogawa, H; Hagiwara, N
Abstract: Background: This study aimed to elucidate whether high-density lipoprotein cholesterol (HDL-C) at 3-month follow-up for patients receiving contemporary lipid-lowering therapy after acute coronary syndrome (ACS) could predict cardiac events. Methods: The HIJ-PROPER study was a multicenter, prospective, randomized trial comparing intensive lipid-lowering therapy (pitavastatin + ezetimibe) and conventional lipid-lowering therapy (pitavastatin monotherapy) after ACS. For the present analysis, the entire cohort was divided into three groups according to HDL-C levels at 3-month follow-up (Group 1, HDL-C ≤43 mg/dL; Group 2, 43–53.6 mg/dL; Group 3; HDL-C ≥53.6 mg/dL). Baseline characteristics and the incidence of the primary endpoint (a composite of all-cause death, non-fatal myocardial infarction, non-fatal stroke, unstable angina pectoris, or ischemia-driven revascularization) were compared among the three groups. Results: The primary endpoint was reported in 34.8%, 30.1%, and 24.6% of patients in Groups 1, 2, and 3, respectively. The incidence of the primary endpoint was significantly higher in Group 1 than in Group 3 (hazard ratio [HR], 1.5; 95% confidence interval [CI], 1.19–1.9; p=0.001). Irrespective of the treatment regimen, Group 1 had a significantly higher rate of the primary endpoint than Group 3 (pitavastatin + ezetimibe therapy: HR, 1.6; 95% CI, 1.12–2.22; p=0.01 and pitavastatin monotherapy: HR, 1.4; 95% CI, 1.05–1.98; p=0.02). These trends remained even after adjustment for baseline characteristics and lipid profiles. Conclusions: Lower levels of HDL-C at 3-month follow-up are associated with higher incidence of the cardiovascular events in patients with acute coronary syndrome receiving contemporary lipid-lowering therapy. Funding Acknowledgement: Type of funding source: None